Solar thermal Applications based on TiO2/Jackfruit peel nanocomposites (International Journal of Food and Nutritional Sciences, 2021)
In the present work synthesize of nanocomposites materials of TiO2/jackfruit peel (JPT) with a mixture of concentration [0.1%; 0.2% ; and 0.3%]. The morphological and structural properties is examined by the XRD & SEM. Prepared material having structure of porous and crystalline with 86%. cobalt (II) chloride; thiourea; and silicon dioxide blended to hybrid nanofluids with different ratios of 10%; 20%; 30%; 40%; 50% and 60%. Those material enhanced the heat transfer inside the solar distiller achieved the productivity of 8.89 L/m2 day.